Bifurcating Time: How Entrepreneurs Reconcile the Paradoxical Demands of the Job. (May 2015) - Miller, Danny; Sardais, Cyrille
Entrepreneurs have been portrayed in paradoxically contrasting ways in the literature. On the one hand, they are said to be intrepid optimists who venture forth with great persistence even in the face of considerable uncertainty and multiple failures; on the other hand, they are held to be realists who are quick to acknowledge the negative realities of their initiatives and adapt very quickly. In order to reconcile these contrasting views, this study tracks in real time the frequent confidential communications of an entrepreneur and his closest consultant and partner during the last 6 months of a failing venture. We are able to gain insight into how by adopting a positive "frame" or consistent mindset about the future, the entrepreneur is able to sustain confidence in the face of significant challenge while at the same time acknowledging and reacting to significant problems in the present. We propose that an intrinsic quality of an entrepreneur is this ability to integrate or reconcile these seeming opposites—to manage paradox, largely by bifurcating time—by making temporal distinctions, and we show how that person simultaneously can be optimistic and realistic, and persistent and adaptive.